Education and training on preparing complementary feeding (MP-ASI) from local ingredients to prevent stunting - Enny Fitriahadi; Esitra Herfanda (Universitas Muhammadiyah Magelang, 2023)
Stunting can occur during fetal development and becomes apparent when the child reaches two years of age. Without proper intervention, such as balanced catch-up growth, stunting can lead to decreased overall growth. This issue is a significant public health concern, associated with an elevated risk of morbidity, mortality, and impediments to both motor and mental development. One proactive approach to address stunting involves education and training in the preparation of Complementary Feeding (MP-ASI) using locally sourced snakehead fish and Moringa leaves. Our observations, conducted until September 2022, revealed that out of 109 children in Sidoarum Village, 34 were identified as stunted. Our initiative commenced with socialization efforts and progressed to educational sessions and practical training in MP-ASI preparation using local ingredients. Participants in these sessions included 40 mothers of toddlers. Notably, 75% of the participants demonstrating high knowledge following the stunting education and MP-ASI preparation training. In addition to enhancing maternal understanding of stunting prevention, our service providers conducted assessments of toddlers' growth and development.